2010
DOI: 10.1016/j.jsps.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a capillary electrophoresis method for the determination of orphenadrine citrate in tablets in the presence of paracetamol

Abstract: A validated method using capillary electrophoresis was developed, for the determination of orphenadrine citrate in its tablet formulations, in the presence of paracetamol. The method employs a running buffer of 30 mM pentane sulfonate sodium, dissolved in 20 mM MOPS buffer pH 7.7. Samples were injected using hydrodynamic sample injection mode (25 mbar, for 25 s), using positive polarity of 25 kV, at a constant temperature of 30 °C. Samples of orphenadrine citrate alone or in mixture solutions with paracetamol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…3.1.2 Effect of buffer pH and strength. Previous studies 33,34 have demonstrated that the pH of buffer solution determines the extent of the analyte ionization and affects the magnitude of the electroosmatic ow (EOF). This effect could be explained in terms of the increase in EOF attained upon increasing pH, due to increased dissociation of silanol groups at the internal surface of the capillary.…”
Section: Resultsmentioning
confidence: 99%
“…3.1.2 Effect of buffer pH and strength. Previous studies 33,34 have demonstrated that the pH of buffer solution determines the extent of the analyte ionization and affects the magnitude of the electroosmatic ow (EOF). This effect could be explained in terms of the increase in EOF attained upon increasing pH, due to increased dissociation of silanol groups at the internal surface of the capillary.…”
Section: Resultsmentioning
confidence: 99%
“…Please insert Figure 1 The literature survey demonstrated that several methods have been carried out for the analysis of PAR & ORP in their pharmaceutical formulation or biological uids. PAR & ORP were determined in their pharmaceutical formulation by using spectrophotometric methods [1][2][3][4][5][6], HPLC methods [7][8][9], TLC and microemulsion HPLC method [10], square wave voltammetric method [11] and capillary electrophoresis method [12]. Several methods have been reported for determination of PAR alone in biological matrix including spectrophotometric methods [13][14][15][16], HPLC methods [17][18][19][20][21], HPTLC method [22], GC method [23] and voltammetric methods [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical methods have been reported on the estimation of paracetamol and orphenadrine citrate either separately or in combination with other drugs in pharmaceutical dosage forms or biological fluids [3][4][5][6][7][8][9] . However, only RP-HPLC 8 , and spectrophotometric 10 methods have been described in the literature for the simultaneous determination of PAR and OPC in their combined formulations, despite the recognized commercial distribution of their tablets.…”
Section: Introductionmentioning
confidence: 99%